How to best address aviation's full climate impact from an economic policy point of view? – Main results from AviClim research project. (June 2016) - Scheelhaase, Janina D.; Dahlmann, Katrin; Jung, Martin; Keimel, Hermann; Nieße, Hendrik; Sausen, Robert; Schaefer, Martin; Wolters, Florian
Highlights: CO2 and non-CO2 species (NOx, contrails, etc.) contribute to aviation's full climate impact. AviClim investigates how to limit aviation's full climate impact. Results show that global emissions trading for all species would be the best option. Costs and impacts on competition could be kept moderate. At the same time, environmental benefits are significant. Abstract: The interdisciplinary research project AviClim (IncludingAvi ation in International Protocols forClim ate Protection) has explored the feasibility for including aviation's full climate impact, i.e., both long-lived CO2 and short-lived non-CO2 effects, in international protocols for climate protection and has investigated the economic impacts. Short-lived non-CO2 effects of aviation are NOx emissions, H2 O emissions or contrail cirrus, for instance. Four geopolitical scenarios have been designed which differ concerning the level of international support for climate protecting measures. These scenarios have been combined alternatively with an emissions trading scheme on CO2 and non-CO2 species, a climate tax and a NOx emission charge combined with CO2 trading and operational measures (such as lower flight altitudes). Modelling results indicate that a global emissions trading scheme for both CO2 and non-CO2 emissions would be the best solution from an economic and environmental point of view. Costs and impacts on competition could be kept at a relatively moderate level and effects on employment are moderate, too. At the same time, environmental benefits are noticeable.